Transient simulation and exergy analysis of a D-type steam boiler with natural circulation during cold start: A case study. (25th June 2022) - Hashemi Beni, Mehdi; Emami, Sobhan; Meghdadi Isfahani, Amir Homayoon; Shirneshan, Alireza; Kalbasi, Rasool
Highlights: Implementing of 3D mathematical model for D-Type boiler furnace. Determining the natural circulation direction for each wall of furnace in the start. The model results compare with experimental data of a D-Type boiler. The sensitivity analysis on the initial water level of the drum is performed. Abstract: It is necessary to utilize an accurate control system in D-type boilers under transient loading. In this paper, a saturated D-Type boiler has been modeled and studied under cold start condition. This type of boiler has two kinds of heat transfer surfaces which are radiative zone (RZ) and convective zone (CZ). Since the furnace shape according to the gas path is not symmetric, the RZ section has been modeled via 3D mesh, and the CZ section has been modeled via the zoning method. The presence of D-shaped tubes in the furnace and different heat absorption of other tubes forced the model to have consisted of four circulation circuits of water in RZ and CZ. According to cold start conditions, inverse flow can occur in circulation circuits which this phenomenon has been studied in this paper. The methodology was included: simultaneous modeling of flue gas side and water side via detail modeling of circulation circuits with exergy analysis, and asymmetric 3D modeling of furnace via mathematical models considering cold start constraints. The comparison of model data against experimental data has shown a maximum deviation of 8.6% for drum pressure during start-up. Also, a sensitivity analysis on the initial water level of the drum in cold-start conditions has been performed by increasing from 200 to 500 and 800 mm; and the results indicated a 4.2% and 10.8%, increase in fuel consumption, respectively. Moreover, the boiler's exergy efficiency reaches a maximum of 60% during cold start-up and declines to 38.2% in steady-state conditions.